Market Reaction and Share Performance Towards the Merger and Acquisition Announcement of 2015-2019 - Puspita*, Gadis Arimbi; Yunita, Irni (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
This study aims to analyze differences in market reactions and performance before and before announcing Mergers and Acquisitions in companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 by measuring differences in Abnormal Return (AR), Trading Volume Activity (TVA), Security Return Variability (SRV), and Actual Return (R) 10 days before and 10 days after the event. The method used is quantitative. The data used are secondary data on daily closing stock prices and the number of shares held during the observation period. The test results show that there is no significant difference in Abnormal Return (AR), Trading Volume Activity (TVA), and Actual Return (R) before and before the event. However, there is a significant difference in the Security Return Variability (SRV) before and before the event. Keywords: Abnormal Return; Trading Volume Activity; Security Return Variability; Actual Return; Merger and Acquisition Penelitian ini bertujuan untuk menganalisis perbedaan reaksi pasar dan kinerja saham Before dan After pengumuman merger dan akuisisi pada perusahaan terdaftar di Bursa Efek Indonesia (BEI) tahun 2015-2019 dengan mengukur perbedaan Abnormal Return (AR), Trading Volume Activity (TVA), Security Return Variability (SRV), dan Actual Return (R) 10 hari Before dan 10 hari setelah peristiwa. Metode yang digunakan adalah kuantitatif. Data yang digunakan adalah data sekunder harga saham penutupan harian dan jumlah saham yang diperdagangkan selama periode pengamatan. Hasil uji menunjukkan tidak ada perbedaan signifikan pada Abnormal Return (AR), Trading Volume Activity (TVA) dan Actual Return (R) Before dan After peristiwa. Namun terdapat perbedaan yang signifikan pada Security Return Variability (SRV) Before dan After peristiwa. Kata Kunci: Return Tidak Normal; Aktivitas Volume Perdagangan; Variabilitas Pengembalian Keamanan; Return Aktual; Penggabungan dan Akuisisi